Emerging Biomaterial Strategies for Giant Cell Arteritis: Challenges and Future Outlook - Balamurugan, Bhavani Sowndharya; Agaram Sundaram, Vickram; Chinnakannu Marimuthu, Mathan Muthu; Anbalagan, Saravanan; Chopra, Hitesh (Scripta Medica, 2026)
Giant cell arteritis (GCA) is a common vasculitis of the big arteries that affects people as they get older and it usually results in potentially serious problems like vision loss and stroke. Steroids remain the cornerstone of GCA treatment, although long-term steroid use is associated with significant adverse effects and a high chance of recurrence. This review will look at biomaterials as a new treatment technique that could help improve GCA management through focused therapy, reduced systemic side effects and facilitated vascular restoration. A comprehensive evaluation of current breakthroughs in biomaterial-based GCA techniques was carried out, with an emphasis on nanoparticles, hydrogels and tissue-engineered scaffolds. The literature was reviewed to determine their therapeutic efficacy, biocompatibility and potential for clinical use. Biomaterials such as nanoparticles and hydrogels have showed promise in controlled drug delivery, allowing for focused treatment at sick artery sites while lowering systemic steroid exposure. Tissue-engineered scaffolds have shown promise for vascular repair and regeneration, at least more effectively than standard methods of treating an injured vessel. However, many problems exist, including maintaining long-term biocompatibility, stability and avoiding immunological responses. Although early preclinical studies have produced encouraging results, clinical translation is still in its infancy. Emerging biomaterials will be a potential area in GCA care, offering new opportunities for treatment efficacy enhancement while reducing side effects. Advanced research in the areas of biocompatibility and immune response challenges should be conducted to ease these promising tactics into clinical practice as a new hope for people suffering from this debilitating condition.